STATE-OF-THE-ART RECENT TECHNOLOGIES, BACKGROUND, TERMINOLOGIES, CHALLENGES: A PRELIMINARY SURVEY ON BIG DATA - C. Esther, S.Keerthana, S.Pradhipa, C.A.Daphine Desona Clemency, M.Joy Priyanka (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
Big data is a future research area acquiring substantial attention from academia and research communities. In advanced technologies, the extents of data generated and stored have dispersed within a short period of time. In context of big data, traditional data techniques and programs are less coherent. They show a slow responsiveness and lack of scalability, performance and accuracy. Subsequently, fast growing rate of data has created many demanding factors like speedy growth of data, transmission speed, data diverse, security and so on. At this point, distinct types of distributions, technologies, applications and latest trends have been developed. This paper explicitly presents the overall analysis on state-of-the-art big data technologies, background, terminologies, technical challenges and review of current approaches. In addition, future research suggestions in the field of big data are determined based on progress and definite open issues in big data analytics. Therefore research directions facilitate the study of domain with improvement of optimal techniques to expose big data.